Proceso de atención de enfermería en adulto con coledocolitiasis. - Mosquera Mindiolaza, Ericka Ibeth (2022)
Choledocholithiasis is defined as the presence of stones or also called calculations that are found in the bile duct or pathway. Among the most common symptoms that can be evidenced is abdominal pain that can be similar to gallstones and sometimes patients can also have jaundice. Endoscopic retrograde cholangiopancreatography is one of the most used procedures for the treatment of choledocholithiasis. The main objective of this case study was to develop the nursing care process in a patient treated at the Specialty Hospital of the Armed Forces No. 1 with a diagnosis of choledocholithiasis. With the medical treatment and the appropriate nursing interventions, the patient was given quality care and warmth, satisfying her needs and achieving an effective recovery.